A novel dual-radar fusion method for improving the cross-range resolution of ISAR imagery. Issue 3 (4th March 2022) - Jiang, Yicheng; Chen, Ruida; Zhang, Yun
ABSTRACT: For the intelligent crossroad with millimetre wave radar, two radars are placed perpendicular to each other to complete the monitoring and identification of vehicles which means the cross-radar can obtain inverse synthetic aperture radar (ISAR) image while the radial radar can not obtain, but the cross-range of a scattering point in ISAR image is equivalent to the radial range of the same point in another radar's view. Thus, the special placement of radar is utilized to improve cross-range resolution in ISAR image. In this letter, a novel dual-radar fusion method for improving ISAR image cross-range resolution for isolated scattering points on target is proposed. First, the range information of scatters is gathered from radial radar based on multiple signal characterization (MUSIC) algorithm. Then, data interpolation and construction of the modulation function will be completed. Finally, the ISAR image cross-range resolution can be improved by fusing the ISAR image obtained from cross-radar and the modulation function. The effectiveness of the proposed method is validated by simulation and experimental results.